Designing for Wellness: How Therapeutic Architecture Can Enhance User Wellbeing in Lekki, Lagos - Adekunle, Ogunnaike; Kesena, David-Mukoro; Dominion, Olofu (International Journal of Research in Interdisciplinary Studies, 2025)
The growing urbanisation of Lekki, Lagos, presents complex challenges to the physical and mental wellbeing of its residents and users. This study investigates how therapeutic architecture can enhance user wellbeing in wellness-focused facilities within this dynamic urban context. Using a quantitative research design, data were gathered from 196 participants drawn from Dew Centre and Happiness Centre through structured questionnaires. The data were analysed using SPSS v.26, applying descriptive and inferential statistics to uncover patterns in user perceptions of key architectural features. Findings revealed that biophilic elements, including natural light, greenery, and visual connections to nature, had a strong positive correlation (r = 0.62, p < 0.001) with users’ sense of calm. Clear pathways and spatial simplicity were also significant predictors of positive emotional outcomes, while complex layouts showed a moderate negative association with feelings of calm (r = -0.38, p = 0.021). Stakeholder-specific preferences varied: healthcare providers prioritised hygiene-compliant materials and functional clarity, while users emphasised privacy, access to daylight, and noise reduction. Based on these results, the study recommends the integration of biophilic design, modular and adaptable spaces, gender- and occupation-sensitive design interventions, and the creation of therapeutic gardens and walking loops within new and existing developments in Lekki. The findings provide an evidence-based framework for architects, planners, and developers seeking to embed wellness into the urban fabric of Lagos, with the goal of fostering healthier, more resilient communities.